2012
DOI: 10.1002/etc.1739
|View full text |Cite
|
Sign up to set email alerts
|

Comparative toxicity of four chemically dispersed and undispersed crude oils to rainbow trout embryos

Abstract: The chronic toxicity of crude oil to fish embryos depends on the chemical constituents of the test oil and on factors that control the exposure of embryos to those constituents. The partitioning of chemicals from oil to water depends on the surface area of oil exposed to water and thus on the susceptibility of oil to be dispersed into droplets. The chronic toxicity of four different crude oils to embryos of rainbow trout (Oncorhynchus mykiss) was measured by exposure to the water‐accommodated fraction (WAF; no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 34 publications
6
38
1
Order By: Relevance
“…Future experiments should identify or rule out any dispersant-nujol interactions. Overall, the effect on medaka embryos of dilbit exposure corresponded to the effects of exposure of fish embryos to various crude oils (Wu et al, 2012Olsvik et al, 2011, refined oils such as heavy fuel oil (Martin et al, 2014;Incardona et al, 2011b), diesel fuel (Schein et al, 2009), and individual PAH and alkyl PAH (Incardona et al, 2006, 2011aTurcotte et al, 2011Lin et al, 2015). The greater apparent toxicity of dilbit CEWAF relative to WAF corresponded to previous observations that chemical dispersion increases the amount of oil that is bioavailable and toxic to fish embryos without any clear indications of interactive toxicity (Adams et al, 2014a).…”
Section: Discussionmentioning
confidence: 94%
“…Future experiments should identify or rule out any dispersant-nujol interactions. Overall, the effect on medaka embryos of dilbit exposure corresponded to the effects of exposure of fish embryos to various crude oils (Wu et al, 2012Olsvik et al, 2011, refined oils such as heavy fuel oil (Martin et al, 2014;Incardona et al, 2011b), diesel fuel (Schein et al, 2009), and individual PAH and alkyl PAH (Incardona et al, 2006, 2011aTurcotte et al, 2011Lin et al, 2015). The greater apparent toxicity of dilbit CEWAF relative to WAF corresponded to previous observations that chemical dispersion increases the amount of oil that is bioavailable and toxic to fish embryos without any clear indications of interactive toxicity (Adams et al, 2014a).…”
Section: Discussionmentioning
confidence: 94%
“…Singer et al (2000) suggested the standard methods for effectively evaluate the toxicity of WAF and CEWAF capable of simulating the oil spill in wild conditions. Although there were several studies on the toxicity of WAF and CEWAF on aquatic organisms (Adams et al, 1999;Gulec and Holdway, 2000;Couillard et al 2004;Koyama and Kakuno, 2004;Fuller et al, 2009;Wu et al, 2012), phototoxicity of oil and oil compounds (Farwell et al, 2006), and the combined effects of UV radiation and dispersant on toxicity of oil (Barron et al, 2003), most of which focused with the early life stage of fishes and shrimps. Researches pertaining to bivalve species are limited (Pelletier et al, 1997;Saco-Álvarez et al, 2008).…”
Section: Hebei Spiritmentioning
confidence: 99%
“…In past, dispersants had adverse effects on ecosystems, but recently developed dispersants contains less toxic effects and accepted as safely applicable. In spite of low toxicity of oil dispersant, it changes the reactivity of hydrocarbons and increases the bioavailability of oil constituents to aquatic organisms so that the toxicity of spilled oil can be increased (Ramachandran et al, 2004;Schein et al, 2009;Wu et al, 2012). Therefore, the effects of UV radiation and oil dispersant must be considered in the assessment of ecotoxicity of spilled oil to aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…These life stages were shown to be sensitive to contaminants, and adverse effects are predictive for long-term toxicity (McKim, 1977;Hutchinson et al, 1998). Several studies investigated adverse effects of the DWH oil spill on the early development of fish (Dubansky et al, 2013;Incardona et al, 2014;RicoMartínez et al, 2013;Wu et al 2012;Denslow et al, 2015). Exposure of embryonic Gulf killifish to field collected sediment resulted in smaller length at hatch as well as bradycardia (Dubansky et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This has the potential to lead to altered responses (RicoMartínez et al, 2013). Wu et al (2012) found that increased toxicity was observed in juvenile rainbow trout (Oncorhynchus mykiss) when fish were exposed to a combination of oil and Corexit compared to oil only. Similarly, exposure to Corexit 9500 and oil elevated the LC 50 by 20-fold compared to crude oil exposure without dispersants in sheepshead minnow (Cyprinodon variegatus) and menidia (Menidia beryllina) (Denslow et al, 2015).…”
Section: Introductionmentioning
confidence: 99%